Regulation of TGF-β1-Induced Pro-Apoptotic Signaling by Growth Factor Receptors and Extracellular Matrix Receptor Integrins in the Liver - Ozaki, Iwata; Hamajima, Hiroshi; Matsuhashi, Sachiko; Mizuta, Toshihiko (Frontiers in Physiology, 2011)
Hepatocellular carcinoma (HCC) often arises from chronically diseased livers. Persistent liver inflammation causes the accumulation of excessive extracellular matrix (ECM) proteins and impairs the liver function, finally leading to the development of HCC. A pleiotropic cytokine, transforming growth factor(TGF)-β, plays critical roles throughout the process of fibrogenesis and hepatocarcinogenesis. In the liver, TGF-β inhibits the proliferation of hepatocytes and stimulates the production of ECM from hepatic stellate cells (HSCs) to maintain tissue homeostasis. During disease progression, both growth factors/cytokines and the ECM alter the TGF-β signals by modifying the phosphorylation of Smad proteins at their C-terminal and linker regions. TGF-β stimulates the expression of integrin, a cellular receptor for ECM, along with an increase in ECM accumulation. The activation of integrin by the ECM modulates the response to TGF-β in hepatic cells, resulting in their resistance to TGF-β-induced growth suppression in hepatocytes and the sustained production of ECM proteins in activated HSCs/myofibroblasts. Both growth factor receptors and integrins modify the expression and/or functions of the downstream effectors of TGF-β, resulting in the escape of hepatocytes from TGF-β-induced apoptosis. Recent studies have revealed that the alterations of Smad phosphorylation that occur as the results of the crosstalk between TGF-β, growth factors and integrins could change the nature of TGF-β1 signals from tumor suppression to promotion. Therefore, the modification of Smad phosphorylation could be an attractive target for the prevention and/or treatment of HCC.